2020
DOI: 10.1155/2020/2792481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Key Parameters Using Deep Convolutional Neural Networks for Airborne Pollution (PM10) Prediction

Abstract: Particulate matter with a diameter less than 10 micrometers (PM10) is today an important subject of study, mainly because of its increasing concentration and its impact on environment and public health. is article summarizes the usage of convolutional neural networks (CNNs) to forecast PM10 concentrations based on atmospheric variables. In this particular case-study, the use of deep convolutional neural networks (both 1D and 2D) was explored to probe the feasibility of these techniques in prediction tasks. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The research demonstrated that the linear model performed worse than the neural network model. With the neural network model, they attained an estimated accuracy of 0.95 [38]. To study the air quality index in Chennai, India, Refs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research demonstrated that the linear model performed worse than the neural network model. With the neural network model, they attained an estimated accuracy of 0.95 [38]. To study the air quality index in Chennai, India, Refs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The behavior of air pollutants varies, as they are affected by various climatic and geographic variables [1,[7][8][9], in this paper we will limit ourselves to the study of particulate matter (PM), which is a classification of pollutants that have begun to generate alerts in growing and overpopulated cities because of their chaotic behavior, which is complicated to model [6,10]. Algorithms such as artificial neural networks (ANN) have demonstrated their versatility in modeling the chaotic behavior of several variables, allowing the prediction of future behaviors with great adaptability to changes in the analysis data [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%